Role of physical load factors in carpal tunnel syndrome - Viikari-Juntura, Eira; Silverstein, Barbara (Scandinavian Journal of Work, Environment & Health, 1999)
Epidemiologic and experimental studies were reviewed to assess the role of postural factors, high handgrip and pinch forces, repetitive hand and wrist movements, external pressure, and vibration in the occurrence of carpal tunnel syndrome (CTS). Forceful repetitive work, vibration, and extreme wrist postures have been associated with CTS in several epidemiologic studies. Experimental studies have shown that certain forearm, wrist, and finger postures, even moderate hand loads and external pressure on the palm, can increase carpal tunnel pressure (CTP) at least temporarily to levels at which nerve viability is threatened. It is concluded that while more research is needed, there is sufficient information to suggest that reducing the duration, frequency or intensity of exposure to forceful repetitive work, extreme wrist postures and vibration is likely to result in a reduction of the incidence or severity of CTS in working populations.
Keywords: epidemiology; experimental study; external pressure; force; postural load; repetitive work; risk factor; vibration